How different is cancer control across Canada? Comparing performance indicators for prevention, screening, diagnosis, and treatment - Rahal, R. (Curr Oncol, 2017)
Meaningful performance measures are an important part of the toolkit for health system improvement. The Canadian Partnership Against Cancer has been reporting on pan-Canadian cancer system performance indicators since 2009—work that has led to the availability of standardized measures that can help to shed light on the extent of variation and opportunities for quality improvement across the country. Those measures include a core set of system indicators ranging from prevention and screening, through diagnosis and treatment, to survivorship and end-of-life care. Key indicators were calculated and graphed, showing the range from worst to best result for the provinces and territories included in the data. There were often significant differences in cancer system performance between provinces and territories. For example, smoking prevalence rates ranged from 14% to 62%. The 90th percentile wait times from an abnormal breast screen to resolution (without biopsy) ranged from 4 weeks to 8 weeks. The percentage of breast cancer resections that used breast-conserving surgery rather than mastectomy ranged from 38% to 75%. Clinical trial participation rates for adults ranged from 0.2% to 6.6%. Variations in performance indicators between Canadian jurisdictions suggest potential differences in the planning and delivery of cancer control services and in clinical practice patterns and patient outcomes. Understanding sources of variation can help to identify opportunities for improvements in the quality and outcomes of cancer control service delivery in each province and territory.